Effect of phenolic hydroxyl groups on inhibitory activities of phenylpropanoid glycosides against lipase. (November 2017) - Wu, Xuli; Feng, Yue; Lu, Yuqin; Li, Yao; Fan, Long; Liu, Lizhong; Wu, Kaimin; Wang, Xinrong; Zhang, Baoshuang; He, Zhendan
Highlights: The inhibition and binding affinities of PPGs for lipase were analyzed. The hydrogen bond plays an important role in the interaction between PPGs and lipase. With increasing phenolic hydroxyl groups on PPGs, the interaction increase. The inhibitory effect of phenolic hydroxyl group is higher at the A-ring than B-ring. Abstract: The phenolic hydroxyl group in polyphenols is a significant structural feature to for understanding their inhibition of lipase. In this paper, we studied four phenylpropanoid glycosides (PPGs) (acteoside, lipedoside A-I, syringalide A 3′-α-l -rhamnopyranoside and osmanthuside B) with different numbers and positions of the phenolic hydroxyl groups in terms of their inhibition of and affinities for porcine pancreatic lipase. The inhibitory effects on lipase were in the order of acteoside (IC50  = 2.17 ± 0.13 mg/ml) > syringalide A 3′-α-l -rhamnopyranoside (IC50  = 3.87 ± 0.21 mg/ml) > lipedoside A-I (IC50  = 4.27 ± 0.22 mg/ml) > osmanthuside B (IC50  = 23.14 ± 0.51 mg/ml). The order of binding affinity to lipase was acteoside > syringalide A 3′-α-l -rhamnopyranoside > lipedoside A-I > osmanthuside B. The hydrogen bond plays an important role in the interaction between PPGs and lipase. With increasing phenolic hydroxyl groups in PPGs, their binding affinities and inhibition for lipase increased.